Challenges of Writing Theses and Dissertations in an EFL Context: Genre and Move Analysis of Abstracts Written by Turkish M.A. and Ph.D. Students - Sükan, Serdar; Mohammadzadeh, Behbood (Frontiers in Psychology, 2022)
Writing a thesis and dissertation is a challenging procedure as one of the requirements of getting a graduate and postgraduate diploma. Writing an abstract like other parts of a thesis or dissertation has its criterion. For this reason, due to globalism, those abstracts written by non-native English speakers may lack some of the features of the abstract genre and move that must be included. This study examines the moves of MA and PhD abstracts written by Turkish students between 2009-2019 Academic Years on Foreign Language Education in Cyprus International University. The data consisted of 50 abstracts chosen randomly from the ELT department. For the analysis, Hyland’s five move model has been used. The study reveals that 25 abstracts did not follow the five moves that Hyland has put forward. Moreover, it can be stated that the absence of some moves in the abstracts may cause restrain for readers to comprehend these studies in terms of communicative purposes.